Shifting focus through a small lens: Discursive and introspective perspectives on the emergence of L2 study emotions - Sampson, Richard J. (Studies in Second Language Learning and Teaching, 2022)
While perennial in the research landscape, empirical work investigating second language (L2) study emotions has proliferated in the past ten years (Dewaele, 2019). Nevertheless, this article argues there is space for more holistic yet detailed, social yet individual perspectives when conducting such research. As one avenue, the paper explores the potential of a “small lens” approach (Ushioda, 2016) to delve into particular emotional events in situ from learner-internal and learner-external points of view. It details an example of such an approach put into practice, in which the author examined the emergence of emotionally significant episodes for English as a foreign language undergraduates in Japan during short conversation sessions. The research explored data from discursive (video-recordings and transcripts of short conversations) and introspective (learner journals) angles. As a result, it was possible to observe the ways in which students’ emotional moves were both afforded by and acted on those of the other through their social interactions, and through interactions with additional aspects of their ongoing psychologies and relationships. The article thus aims to promote further situated L2 emotion research examining the dynamic interplay between various aspects of learners’ psychologies and the co-formed social context.